The heart in systemic autoimmune diseases - Doria, A. (Andrea); Pauletto, Paolo, 1947- (Handbook of systemic autoimmune diseases, 2004)
This first volume represents the state-of-the-art in the field of cardiovascular disease and autoimmune rheumatic diseases. Systemic autoimmune diseases comprise a family of conditions that share common pathogenetic mechanisms as well as a multi-organ involvement including the heart. This volume has been subdivided into three parts. In the first part, the immune mechanisms involved in cardiac damage have been considered. The role of proinflammatory and regulatory cytokines in driving an autoimmune response to cardiac self-tissues has been analysed. Moreover, the prevalence, the clinical meaning and the hypothetical pathogenicity of a broad spectrum of organ and non-organ specific autoantibodies have been discussed in detail. In the second part of the volume, the role of humoral and innate immunity in promoting the development of atherosclerotic plaque has been extensively reviewed, along with the newly discovered anti-inflammatory properties of statins. These two parts of the volume deal with exciting aspects of this topic, suggesting a very close connection between heart diseases and immunology. Finally, in the third part, the cardiac manifestations observed in the major systemic autoimmune conditions have been comprehensively examined. This book yields an impressive body of well ordered information, highlighting key references and summarising the experience of a selected panel of distinguished physician-scientists actively involved in the field of cardiovascular disease and systemic autoimmunity.